اختصاص مجلس الدولة ضمن أحكام القانون 22-11 - بوغزالة ، محمد إيمان; مكاوي ،إنتصار (جامعة الوادي University of El Oued, 2024)
تتمثل هده الدراسة البحثية في تسليط الضوء على اهم التعديلات والمستجدات التي جاء بها القانون العضوي 22-11 الذي يعدل ويتمم القانون العضوي98-01 المتعلق بتنظيم مجلس الدولة تنظيمه وسيره اختصاصته. تبين لنا من خلال هده الدراسة ان التعديل الاخير لقانون العضوي 22-11 جاء بتعديلات مهمة تخص اختصاصات مجلس الدولة تضمنت مراجعة واعادة ضبط اختصاصته اذ تم اخراج اختصاص اول واخر درجة وكذا وظيفة الطعن بالاستئناف من اختصاصات مجلس الدولة مع إبقاء استثنائيا على اختصاص الاستئنافي لمجلس الدولة في مجال محدد كما تضمنت هده التعديلات ايضا مراجعة وظيفة الطعن بالنقض وجعله يتفرغ اكثر لدوره المنوط به المتمثل في توحيد الاجتهاد القضائي في المادة الإدارية. This research study aims to shed light on the most important amendments and developments brought about by Organic Law 22-11, which amends and complements Organic Law 98-01 relating to the organization of the State Council, its organization and the conduct of its jurisdiction. Through this study, we found that the latest amendment to the Membership Law 22-11 brought important amendments related to the powers of the State Council, which included reviewing and resetting its jurisdiction, as the first and last level jurisdiction, as well as the function of appeal, were removed from the powers of the State Council, while keeping exceptionally the appellate jurisdiction of the State Council in A specific field. These amendments also included a review of the cassation appeal function It made him devote more time to his assigned role of unifying judicial jurisprudence in administrative matter
ماستر اداري